2019
DOI: 10.1126/scisignal.aaw1347
|View full text |Cite
|
Sign up to set email alerts
|

TLR7 and TLR8 activate distinct pathways in monocytes during RNA virus infection

Abstract: Human blood CD14+ monocytes are bone marrow–derived white blood cells that sense and respond to pathogens. Although innate immune activation by RNA viruses preferentially occurs through intracellular RIG-I–like receptors, other nucleic acid recognition receptors, such as Toll-like receptors (TLRs), play a role in finely programming the final outcome of virus infection. Here, we dissected how human monocytes respond to infection with either Coxsackie (CV), encephalomyocarditis (EMCV), influenza A (IAV), measles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
128
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(135 citation statements)
references
References 117 publications
5
128
1
1
Order By: Relevance
“…With regard to expression in cells, TLR7 is expressed at relatively high levels in plasmacytoid dendritic cells, eosinophils, neutrophils and B cells, with TLR8 being expressed in myeloid dendritic cells, neutrophils and monocytes (Marques & Williams, 2005), suggesting that the function of TLRs is influenced or divided by cell differentiation or localization. Furthermore, recent studies have suggested that TLR7 and TLR8 differentially activate downstream pathways (Marcken et al, 2019) and that TLR8 is upregulated and works compensatorily in TLR7 À/À mice (Awais et al, 2017).…”
Section: General Features Of Tlr8mentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to expression in cells, TLR7 is expressed at relatively high levels in plasmacytoid dendritic cells, eosinophils, neutrophils and B cells, with TLR8 being expressed in myeloid dendritic cells, neutrophils and monocytes (Marques & Williams, 2005), suggesting that the function of TLRs is influenced or divided by cell differentiation or localization. Furthermore, recent studies have suggested that TLR7 and TLR8 differentially activate downstream pathways (Marcken et al, 2019) and that TLR8 is upregulated and works compensatorily in TLR7 À/À mice (Awais et al, 2017).…”
Section: General Features Of Tlr8mentioning
confidence: 99%
“…Meanwhile, the relationship between TLR8 and autoimmune diseases has received considerable attention (Farrugia & Baron, 2017), with well known examples including systemic lupus erythematosus (Devarapu & Anders, 2018) and rheumatoid arthritis (Elshabrawy et al, 2017). Since TLR8 (and TLR7) senses and responds to various kinds of RNA viruses (Marcken et al, 2019;Coch et al, 2019), TLR8 deficiency has been proposed to cause viral infections; however, it has been reported that TLR8 deletion accelerates autoimmunity in mice (Tran et al, 2015).…”
Section: Tlr8 As a Therapeutic Targetmentioning
confidence: 99%
“…Their primary function is to activate innate immune responses while they are also involved in facilitating adaptive immune responses (7). Different TLRs differ in their expression in various target cells and exert distinct functions by activating varied immune cascades (7)(8)(9). In the TLR family, several TLRs have been studied as cancer drug targets such as TLR2, 4, 7, 8 and 9 (7,(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…This virus was chosen because of its ability to model the innate immune activation pathways of prevalent respiratory RNA viruses and because it is safe to use in a high-throughput, biosafety level one laboratory. 23,24 The virus infected the monocytes and macrophages, which subsequently created a highly inflamed environment for the lymphocytes and other PBMCs. The differences between the young and old immune response were captured in our system's multi-phenotype aging profile of viral response, which contained dozens of features measuring changes in cell composition, physical cell-to-cell interaction, organelle structure, cytokine levels, and other hidden complexities that contribute to age-related dysfunction.…”
Section: Introductionmentioning
confidence: 99%